PENGGUNAAN PUPUK N P K PADA TANAH BEKAS PEMBERIAN BAHAN ORGANIK TERHADAP PERTUMBUHAN DAN HASIL KACANG HIJAU - F. Hulopi (Universitas Tribhuwana Tunggadewi, 2012)
One of the factor causing the low of productivity of mungbean in Indonesia is soil fertility, seed, planting, protection, and irrigation. The existance of organic element absorbed by plants is one of the factor affecting the plant production. This research aimed to find out the effect of N P K fertilizer on the residual effect of organic substance derived from hull of rice and chicken manure to the growth and result of mungbean. The experiment was using Split Plot Design by the main plot was the level of residual of organic substance (B), consisted of B1: hull of rice 10 t/ha and B2: chicken manure 10 t/ha. As the sub-plot was: dosage of N P K fertilizer (N) consisted of (N1): without fertilizer, (N2): 33 kg P2O5 ha-1, 37 kg K2O ha-1, (N3): 23 Kg N ha-1N, 37 Kg K2O ha-1, (N4): 23 Kg N ha-1N, 33 Kg P2O5 ha-1,(N5): 23 Kg N ha-1N, 33 Kg P2O5 ha-1, 35 Kg K2O ha-1. The variables observed were height of plant, sum of leaf, dry weight of plant, small pimple root of plant, wide of leaf, and LAI (Leaf Area Index), sum of pea, weight of pea, weight of 100 peas, dry seed per ha, sum of harvest plant, and weight of pea. The result showed that N P K treatment given to the residual of organic substance of chicken feces or hull of rice did not give a significant effect. Data indicated that N P K fertilizer increase the growth and yield of mungbean. The complete N P K fertilizer dosage (N5) given to residual of organic substance of chicken manure of 10 t/ha could increase the yield of ha-1dry seeds